Nickel‐Catalysed Bis‐Allylation of Activated Nucleophiles with Allyl Alcohol. Issue 6 (29th January 2016) - Blieck, Rémi; Azizi, Mohamed Salah; Mifleur, Alexis; Roger, Maxime; Persyn, Clément; Sauthier, Mathieu; Bonin, Hélène
Abstract: Nickel‐based catalysis allows the efficient bis‐allylation of soft nucleophiles with allylic alcohols. The reaction is best promoted by a combination of Ni(cod)2 (cod = cyclooctadienyl) and diphenylphosphinobutane under additive‐free conditions. Alternatively, nickel(II) precursors can be used provided that a reductant is used to generate the nickel(0) species. The NiCl2 /Zn combination is particularly simple, and can advantageously replace the use of the more air‐sensitive Ni(cod)2 precursor. The scope of the reaction was studied with nucleophiles and allylic derivatives suitable for bis‐allylation reactions. Abstract : The nickel catalysed allylation of soft nucleophiles with allyl alcohol gives bis‐allylated derivatives in high yields. Nickel(0) precursors are accessible from the in‐situ reduction of nickel(II) salts